SERENDIPITOUS DISCOVERY OF HYPERCALCEMIA IN PREGNANCY IN A PATIENT WITH ASYMPTOMATIC BRADYCARDIA ON BETA BLOCKER - Cheah, Jean Mun; Chan, Pei Lin (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hypercalcemia in pregnancy is uncommon and the diagnosis is challenging due to its nonspecific symptoms which may mimic those of pregnancy. The risk of adverse outcomes for the mother and neonate is significant and should be identified earlier. CASE We report a case of a patient with parathyroid-dependent hypercalcemia diagnosed in the third trimester of pregnancy with subsequent complications necessitating emergency caesarean section at 35 weeks of gestation. A 30-year-old pregnant female with chronic hypertension presented at 30 weeks of gestation with asymptomatic bradycardia while on treatment with a beta blocker. She also complained of abdominal discomfort for the past week. On examination, her heart rate was 40-50 beats per minute with no other remarkable findings. Laboratory investigations revealed parathyroid hormone-dependent hypercalcemia with a serum calcium of 2.9 mmol/L and a parathyroid hormone level of 13.3 pmol. 24-hour urine calcium/creatinine clearance ratio was 0.06 and 25-hydroxyvitamin D level was adequate at 80.81 nmol/L. Neck ultrasonography was negative for parathyroid adenoma. Patient was admitted for hydration however due to persistent hypercalcemia, cinacalcet 25 mg daily was commenced at 33 weeks of gestation. Serial foetal growth scans demonstrated a small for gestational age (SGA) fetus. She presented at 35 weeks of gestation with severe preeclampsia, pancreatitis and serum calcium level of 3.03 mmol/L, requiring an emergency caesarean section. A baby boy, weighing 1970 g, was delivered without any calcium disturbances observed. Patient’s calcium levels remained elevated post-partum, requiring saline hydration and subcutaneous calcitonin. Her serum calcium level normalised over the next few days after a dose of pamidronate was given at day 4 post-partum. CONCLUSION Hypercalcemia in pregnancy may result in significant maternal and foetal complications. A high index of suspicion is required for early diagnosis and institution of treatment to improve maternal and foetal outcomes.